A novel extraction method for analysing available sulfamethoxazole in soil. Issue 3 (16th March 2019) - Li, Qianwen; Wang, Yixiang; Cao, Haiyan; Cui, Shiyao; Su, Yuhong
ABSTRACT: A novel extraction method was established to determine the water-extractable (available) content of sulfamethoxazole (SMX) in soil. The SMX imprinted polymers (MIPs) were synthesised and the performance was evaluated by Fourier transform infrared spectroscopy, scanning electron microscopy and binding experiments. Results showed that the MIPs exhibited good selectivity for SMX, so the MIPs were applied as a sorbent. SMX in soil was extracted by water, sorbed from the extract to MIPs and analysed with a high performance liquid chromatography (HPLC) after its desorption from MIPs. Meanwhile, the classic organic solvent extraction was employed to measure the total SMX content in soil. Results showed that when SMX level in spiked soils varying from 1.0–500 μg kg −1, the observed recoveries of available SMX contents ranged from 63.27 ± 3.11% to 82.11 ± 2.77% ( n = 3), while the total SMX varied between 89.59 ± 1.65% and 97.64 ± 3.92% ( n = 3). The detection limit of the developed method for SMX in soils was 0.05 μg kg −1 . Available SMX contents in five field soil samples ranged from 0.13 to 4.14 μg kg −1, which were only 0.35–25.40% of the respective total SMX contents. Results from this study manifest the importance of the extents of SMX immobilisation with different soils for assessing SMX's ecological and human health risks.